Pemetaan Prasarana Perhubungan di Kota Banjarmasin dengan Pemanfaatan Sistem Informasi Geografis - Achiruddin, Ibni (Lambung Mangkurat University Press, 2025)
As a major city in South Kalimantan Province, Banjarmasin has a high population density of 6,769 people per square kilometer and a high level of mobility, with an average of 197,756 vehicles entering and exiting the city. This demands the provision of quality public services—particularly in the transportation sector. To meet these needs, the Banjarmasin City Transportation Agency must ensure the availability of adequate transportation infrastructure, such as piers, river shelters/stops, and public transportation stops, supported by effective asset management. One approach to enhancing this management is through the use of Geographic Information Systems (GIS) for mapping transportation infrastructure. Quantum GIS (QGIS), an open-source and freely available software, is used for spatial data processing. Mapping data indicates that North Banjarmasin District has the highest concentration of transportation infrastructure, with 18 units. Out of the total 63 transportation infrastructure units in the city, 16 are owned by the South Kalimantan Provincial Government. The use of GIS provides a strategic solution for managing transportation infrastructure assets, enabling better monitoring, planning, maintenance, and inventory control.